Fabrication of pbs films for air mass filter of solar simulator - Hilmi, Isom; Kusuma, Damar Yoga; Soetedjo, Hariyadi; Hidayah, Qonitatul; Salamah, Umi (Universitas Gadjah Mada, 2024)
The production of solar panels is continuously increasing due to increasing demands at industrial and residential levels. This also leads to an increasing demand for solar simulator testing tools. A solar simulator is a tool to assess a solar panel's performance in lab and industry scales. One of the main components of the solar simulator is the Air Mass Filter (AMF). The primary function of AMF is to remove unwanted wave bands from the solar simulator light source (e.g., Xe arc lamp) so that the filtered spectrum is commensurate to that of solar irradiation. An AMF can be produced by fabricating a thin material layer on a transparent substrate like glass. The film would absorb certain wave bands in different ways. This paper reports the fabrication of the chalcogenide PbS thin films for applying AMF. The thermal evaporation technique is used for the film fabrication. PbS is known for its versatility for applications in different optical devices due to its tailorable optical properties. Different amounts (in grams) of PbS source powders are used to deposit the PbS thin films. The optical properties of the films are then examined using UV-Vis spectroscopy. The distributions of the transmittance intensity of the Xe-arc-lamp light with and without the use of the films as an optical filter are then examined using a solar simulator. From the experiments, the film deposited using a 0.012 g PbS powder source is regarded as the optimum one regarding the transmittance intensity distribution.